Determinan Gangguan Fungsi Paru Pekerja Terpapar Silika: Systematic Review - Sunindy Wahyunita; Nikie Astorina Yunita Dewanti; Mursid Raharjo (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: Chronic obstructive pulmonary disease is the third leading cause of death in the world. At least 10-20% of chronic obstructive pulmonary disease cases are found in the work environment. One of the causes of lung function disorder suffered by workers is due to inhalation of silica dust. Objectives:To identify the determinants of lung function disorder in workers exposed to silica dust. Research Metodes: Systematic quantitative review that was implemented through a meta-analysis study with initial search results for articles matched to the title and abstract was 44 articles and it was eliminated by using inclusion criteria resulting 20 articles. The publication year of the articles was 2007-2020 and has been indexed by Garuda Dikti, SINTA, DOAJ and Scopus. Results: The number of samples from the combined study of 20 articles was 2.561 workers that 33% of the sample had lung function disorder. The p value for each variable included age p= 0,001, sex p= 0,854, nutritional status p= 0,033, inhaled dust level p= 0,007, working period p= 0,000, length of exposure p= 0,027, history of lung disease p= 0,880, exercise habit p= 0,098, PPE use p= 0,004, and smoking habit p= 0,014. Conclusion: The variables as determinant with the greatest risk of pulmonary function disorder were individual smoking habit and work environment factors.